(untitled) (Al-Aasar, 2026)
In Islamic history, the Mawali played a significant role in the promotion and dissemination of Islamic sciences. The Mawali originating from Sindh also demonstrated their abilities in the religious, intellectual, political, and social spheres within the Islamic society. The present article offers a research-based and analytical study of the role and contributions of the Sindhi Mawali. The study reveals that the Sindhi Mawali rendered remarkable services particularly in the fields of Hadith studies, narration (riwayah) and critical evaluation (dirayah), teaching, as well as authorship and compilation. Similarly, they also held an influential position in political and social domains. Their contributions not only strengthened the intellectual tradition of Sindh but also played an important role in reinforcing the scholarly heritage of the entire Muslim world.